EP-488 Pre-operative electronic checklists as a systematic method to improve patient care. (9th August 2022) - Bhat, Srushti; Al Yasen, Nada; Perikleous, Periklis; Lau, Kelvin
Abstract: Aims: The COVID-19 pandemic has resulted in major changes in pre-operative assessment, as consultations became conducted over the telephone, and pre-operative tests carried out a few days before surgery to coincide with the COVID testing visit. This increased the chances for preoperative tests to be missed. A recent audit in our unit revealed missed investigations just before surgery. A checklist was introduced to identify issues early and help reduce avoidable delays. Methods: An audit was performed for completeness of preoperative preparations. A pre-operative checklist was created to include pre-operative investigation reports, routine laboratory results, proof of COVID-19 swabs and vaccination records, correct details on the theatre lists, signed consent forms with clearly visible patient marking. The checklist was launched and the team, including doctors and nurses, were educated on its value in improving patient care. Results: The implementation of electronic pre-operative checklists resulted in an immediate improvement of care, with preliminary results showing issues with a potential of causing delays being promptly identified and addressed. Late identification of issues could not be entirely avoided; however, this was discussed with team members, further education was provided, and data collection continues, to ensure good practice is sustained. Conclusion: COVID-19 has reduced the time for hospital visit and face to face interactions, but this created the opportunity for missed tests and processes leading to delays and cancellation of surgery. The checklist in our case has proven useful in identifying issues early and promptly managing potential delays in patient care.